Introduction - Broy, Nikolas; Schumann, Matthias (Twentieth-Century China, 2024)
This essay introduces a special issue of Twentieth-Century China that explores the evolution of religiously motivated vegetarianism in Chinese societies from the late imperial period until today, with a focus on the twentieth century. Drawing on ancient practices of fasting and Mahāyāna Buddhist dietary rules, this vegetarianism quickly evolved into a widely accepted form of moral self-cultivation in many religious contexts, one that was intrinsically related to morality, self-actualization, notions of karma and retribution, and ritual purity. Since the late nineteenth century, the impacts of increasing transnational entanglements, new ideas, and changing food practices have subtly transformed this tradition: these transformations include an engagement with global animal protection movements in the wake of the First World War and contemporary attempts to integrate concerns about global warming, food safety, and environmentalism into the discourse. By looking at three specific cases, the special issue traces the persistence and evolution of vegetarian concepts and practices in Chinese societies from the late imperial period until today.